Repeated adrenaline doses and survival from an out-of-hospital cardiac arrest. (May 2019) - Fothergill, Rachael T.; Emmerson, Amber C.; Iyer, Rajeshwari; Lazarus, Johanna; Whitbread, Mark; Nolan, Jerry P.; Deakin, Charles D.; Perkins, Gavin D.
Abstract: Background: Adrenaline is the primary drug of choice for resuscitation from out-of-hospital cardiac arrest (OHCA). Although adrenaline may increase the chance of achieving return of spontaneous circulation (ROSC), there is limited evidence that repeated doses of adrenaline improves overall survival, and increasing evidence of a detrimental effect on neurological function in survivors. This paper reports the relationship between repeated doses of adrenaline and survival in a cohort of patients attended by the London Ambulance Service in the United Kingdom. Methods: A retrospective review of OHCA treated by the London Ambulance Service over a one year period. Patients aged ≥18 years who received one or more doses of adrenaline (1 mg bolus) during resuscitation were included in the analyses. Outcomes described are survival to hospital discharge and survival to one year post-arrest. Results: Over the one year study period, 3151 patients received adrenaline during OHCA. A significant inverse relationship was found between increasing cumulative doses of adrenaline and survival both to hospital discharge and one year post-arrest. No patients survived after receiving more than ten adrenaline doses. Conclusion: Our study indicates that repeated doses of adrenaline are associated with decreasing odds of survival. There were no survivors amongst patients requiring more than 10 doses of adrenaline.